Peranan Intervensi Sosial Dalam Pencegahan Kenakalan Remaja - Amanda Eliza Fitriani; Asla Hanifah Putri; Christiano Ronaldo Suseno; Tugimin Supriyadi (Jurnal Psikologi, 2025)
Juvenile delinquency is a social phenomenon that is increasing in various communities and has a significant impact on the lives of individuals and the surrounding environment. Factors that cause juvenile delinquency include psychological, social and environmental aspects, which pose challenges in handling it. This research aims to identify the role of social intervention in preventing juvenile delinquency and analyzing effective strategies in reducing deviant behavior. The method used is a literature study regarding various forms of social intervention, such as character education, skills training programs, and community activities. The research results show that comprehensive social intervention, involving family, school and community, has proven to be effective in forming positive behavior in adolescents and preventing acts of delinquency. With an integrated approach, it is hoped that efforts to prevent juvenile delinquency can be more optimal in creating a safe and supportive environment for adolescent development.